[PP.25.09] POSSIBLE ROLE OF CYTOCHROME P-450 EICOSANOIDS IN HEMODYNAMIC MODULATION IN A GROUP OF OBESE CHILDREN. (September 2016) - Bonafini, S.; Tagetti, A.; DalleVedove, F.; Benetti, M.V.; Schunck, W.H.; Rothe, M.; Antoniazzi, F.; Maffeis, C.; Minuz, P.; Fava, C.
Abstract : Objective: Obesity in children is an increasing health emergency and is often accompanied by other metabolic and hemodynamic disorders such as hypertension. Arachidonic acid (AA), the major omega-6 PUFA (n-6-PUFA), could be metabolized by cytochrome P-450 (CYP450) to vasoactive and natriuretic eicosanoids, such as epoxyeicosatrienoic acids (EETs). Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), the biologically more relevant omega-3 polyunsaturated fatty acids (n-3 PUFA), may compete with n-6 PUFA for CYP450 metabolism, thus modulating eicosanoids production. Design and method: In this cross-sectional observational study we investigated the possible role of CYP450 metabolites of AA/EPA/DHA in BP modulation and vascular function in obese children. Seventy overweight (n = 4)/obese (n = 66) children (BMI > 90° percentile), aged 5–17 y, underwent ambulatory (ABPM) and office BP measurement and vascular function tests (flow mediated dilatation, FMD, by ultrasound and Stiffness Index, SI, by digital photoplethysmography). N-3 and n-6 PUFA in erythrocytes membranes were measured by gas-chromatography and plasma eicosanoids by LC-ESI-MS/MS. Results: An inverse correlation was found between n-6-PUFA and ambulatory daytime-SBP (r: -0.245; p: 0.046). Indeed, n-3 PUFA, but not n-6-PUFA, showed an inverse correlation with SI (r:-0.288; p: 0.021) which was in turn related to BP (office DBP, r: 0.248; p: 0.046). Dihydroxyeicosatrienoic acids (DHETs), inactive metabolites of EETs, were associated with both ambulatory and office SBP levels and their z-scores (24-hour-SBP r: 0.364, p: 0.002; z-score-24-hour SBP r: 0.328, p: 0.007; daytime-SBP r: 0.347, p: 0.004; z-score-daytime-SBP r: 0.335, p: 0.006; nighttime-SBP r: 0.280 p: 0.026; office SBP r: 0.289, p: 0.016). Epoxydocosapentaenoic acids (EDPs), derived from DHA via CYP450-epoxygenase, were directly correlated to n-3 PUFA (r: 0.364; p: 0.027) and inversely to SI (r: −0.365; p: 0.031). Conclusions: Our data suggest a positive effect of n-6 PUFA on BP, at least partially mediated by CYP-derived metabolites. Indeed the relation between plasma DHETs and BP might reflect the loss of the protective actions of EETs. Cardiovascular protective effect of n-3-PUFA could depend on their action on arterial stiffness, probably through epoxymetabolites of DHA.